2022
DOI: 10.1002/cti2.1379
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic classification of anti‐SARS‐CoV‐2 antibody responses improves seroprevalence estimates

Abstract: Objectives Population‐level measures of seropositivity are critical for understanding the epidemiology of an emerging pathogen, yet most antibody tests apply a strict cutoff for seropositivity that is not learnt in a data‐driven manner, leading to uncertainty when classifying low‐titer responses. To improve upon this, we evaluated cutoff‐independent methods for their ability to assign likelihood of SARS‐CoV‐2 seropositivity to individual samples. Methods Using robust EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The interpretation of the vaccination efficacy based on serological responses bears certain limitations, such as highly variable antibody titers and kinetics among individuals ( 15 , 16 ). The strict cutoff values that are being applied by most antibody tests may not efficiently classify the seropositivity as negative control values may overlap true positive low-titer values ( 17 ). Furthermore, it is crucial to investigate virus-neutralizing antibody responses in vaccinated individuals, including those after lung transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the vaccination efficacy based on serological responses bears certain limitations, such as highly variable antibody titers and kinetics among individuals ( 15 , 16 ). The strict cutoff values that are being applied by most antibody tests may not efficiently classify the seropositivity as negative control values may overlap true positive low-titer values ( 17 ). Furthermore, it is crucial to investigate virus-neutralizing antibody responses in vaccinated individuals, including those after lung transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…There, they found that in house Region Västerbotten had the highest sensitivity and specificity of all assays tested [23]. For this reason, the assay was subsequently used on venous blood samples for probabilistic classification of anti-SARS-CoV-2 antibody responses [24].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by us, and by independent studies by the Swedish Public Health Agency, our assay for detection of S-specific IgG had the highest standard with regards to sensitivity and specificity (17). For this reason, the assays was subsequently used on venous blood samples for probabilistic classification of anti-SARS-CoV-2 antibody responses (18).…”
Section: Discussionmentioning
confidence: 99%